CAMPUR KODE EKSTERN DALAM NOVEL AIR MATA TERAKHIR BUNDA DAN IMPLEMETASINYA PADA PENUMBUHAN SIKAP POSITIF TERHADAP BAHASA INDONESIA - Nurulanningsih, Nurulanningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2023)
ABSTRACT This study aims to describe the external code-mixing in the novel Air Mata Akhir Bunda. In line with the research objectives, the research method used is qualitative. Data collection techniques using documentation techniques and data analysis using intralingual matching techniques. Based on the results of data collection, it was found that the external code mixing in the novel Air Mata Akhir Bunda was the insertion of words and phrases from English. The insertion of words is 21 words and the insertion of phrases is 11 phrases. The factor causing the external code mixing is the use of terms that are popular in the community. To foster a positive attitude towards the Indonesian language, the use of these terms from English can be avoided, considering that the use of these terms from English has been absorbed into the Indonesian language. Keywords: Code Mixing, Novel, Language Attitude